Nitrous oxide abuse and associated neurological diseases - Kongkiat Kulkantrakorn; Patis Chunhachatrachai; Wuttipat Kulkantrakorn (BMC Neurology)
Abstract Objectives Nitrous oxide has long been used as an anesthetic agent. The recreational use and abuse are rapidly increased in Western countries and lead to many neurological complications. Methods Retrospectively review of seven patients. Results Seven patients aged 19–32 years, mean 22.6 years. They inhaled nitrous oxide between 1 month to 1 year prior to the symptom onset. They all presented with acute or subacute ataxia or motor, and sensory dysfunction. The two had coexisting encephalopathy. Electrodiagnosis showed sensorimotor axonal polyneuropathy. All patients had borderline or low serum vitamin B12 level. Two had high serum homocysteine or methylmalonic acid levels. Cervical spine MRI in two patients showed posterior column lesion. At average 2 month-follow up, all patients had minimal improvement. While at more than 6 month-follow up, most patients had moderate to complete recovery. Conclusion Seven patients with nitrous oxide induced neurological disease are reported. All patients present with acute myelopathy and sensorimotor polyneuropathy. Short term outcome is generally not favorable while long term outcome shows remarkable improvement.